The impact of Potocki-Lupski syndrome on sibling relationships - Antunes, Marta; Ferraz de Liz, Mariana; Correia , Zulmira (BIRTH AND GROWTH MEDICAL JOURNAL, 2023)
Introduction: Potocki-Lupski syndrome is a condition characterized by cognitive, behavioral, and medical manifestations caused by 17p11.2 duplication encompassing the RAI1 gene. Due to the significance that sibling relations acquire throughout life, changes in the health and functioning of one sibling affect the others. Case report: A 14-year-old boy, healthy sibling of a girl with Potocki-Lupski syndrome, attended the Child and Adolescent Psychiatry consultation due to maternal concerns about the impact of the sister’s disease on his well-being. On observation, despite looking relatively well adapted to the sister‘s condition, the boy showed sadness and shame regarding some of the sister‘s behaviors, particularly when occurring in public places, and great guilt towards them. Discussion/conclusion: The impact of the intellectual disability of a child on healthy siblings comprises negative and positive experiences. Therefore, it should be assessed in light of a network of influences and idiosyncrasies characteristic of family relationships.